2005
DOI: 10.1182/blood-2005-03-1281
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils rapidly migrate via lymphatics after Mycobacterium bovis BCG intradermal vaccination and shuttle live bacilli to the draining lymph nodes

Abstract: The early innate response after Mycobacterium bovis bacille Calmette-Gué rin (BCG) vaccination is poorly characterized but probably decisive for subsequent protective immunity against tuberculosis. Therefore, we vaccinated mice with fluorescent BCG strains in the ear dorsum, as a surrogate of intradermal vaccination in humans. During the first 3 days, we tracked BCG host cells migrating out of the dermis to the auricular draining lymph nodes (ADLNs). Resident skin dendritic cells (DCs) or macrophages did not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
313
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(342 citation statements)
references
References 33 publications
(42 reference statements)
17
313
3
5
Order By: Relevance
“…Bacteria were thawed, sonicated, washed and diluted in PBS before immunizations and infections. Green and red fluorescent BCG expressing either eGFP or DsRed was a kind gift from Nathalie Winter [5]. Antigens rTB10.4 was produced in E. coli as described earlier [24].…”
Section: Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria were thawed, sonicated, washed and diluted in PBS before immunizations and infections. Green and red fluorescent BCG expressing either eGFP or DsRed was a kind gift from Nathalie Winter [5]. Antigens rTB10.4 was produced in E. coli as described earlier [24].…”
Section: Bacteriamentioning
confidence: 99%
“…Cells stained with F4/80 were washed in FACS-buffer after surface staining with primary antibodies and secondarily stained with streptavidin conjugated PerCp-Cy5. 5.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Earlier studies indicated that neutrophils were able to present exogenous antigen to CD8+ T-cells [7] and recent data have shown also antigen-presentation to Th1 and Th17 cells [2]. In confocal microscopic studies neutrophils migrating with fluorescently labeled pathogen were observed in draining lymph vessels [1] and lymph nodes [21]. Moreover, the chemokine receptor CCR7 has been identified as a key player in directing neutrophil migration from the interstitium to the draining lymph nodes [6].…”
Section: Interaction With Other Immune Cellsmentioning
confidence: 96%
“…Cell attachment to substrate per se may participate to the increase of immune activity and respiratory burst. In mammals, immune cells are known to migrate rapidly towards the site of infection (Abadie et al 2005;Chtanova et al 2008;Germain et al 2012). Interestingly, ex vivo explant experiments give evidence for accelerated random migration of immune cells, at rates of 8 lm min -1 , similar to interstitial velocities reported for neutrophils at sites of inflammation (Graham et al 2009;Kreisel et al 2010).…”
Section: Discussionmentioning
confidence: 65%